Peptide secondary structures in the gas phase: consensus motif of N-linked glycoproteins. - Cocinero, E; Stanca-Kaposta, E; Gamblin, D; Davis, B; Simons, J (2009)
The possibility of secondary structure acting as a primary determinant in nature's choice of the consensus sequon, NXS/T in all N-linked glycoproteins, has been addressed by determining the intrinsic secondary structures of the capped oligopeptide, Ac-NGS-NHBn, and two "mutants", Ac-QGS-NHBn and Ac-NPS-NHBn, by use of infrared laser ion dip spectroscopy in the gas phase coupled with ab initio and density functional theory calculation. Their global minimum energy conformations, exclusively or preferentially populated in all three peptides, display marked differences. NGS adopts an open, S-shaped backbone conformation rather than the C(10) "Asx" turn structure that all previous measurements have identified in solution; the difference can be related to the high dipole moment of the "Asx" conformation and structural selection in a polar environment. QGS adopts a similar but more rigid backbone structure, supported by markedly stronger hydrogen bonds. NPS adopts an Asx turn coupled with a C(10) beta-turn backbone conformation, a structure also adopted in a crystal environment. These and other more subtle structural differences, particularly those involving interactions with the carboxamide side chain, provide strong evidence for the operation of structural constraints, and a potential insight into the unique reactivity of the asparagine side chain toward enzymatic glycosylation.